Three-Year Review Of The Marine Minerals Technology Center - Continental Shelf Division - Malcolm J. McPhersqn; Dorothy B. Niell (International Marine Minerals Society, 1991)
In its first three years of operations, the in-house programs of the continental Shelf Division of the Marine Minerals Technology Center (MMTC/CSD) have focused on the development of drill systems - technology and the improvement of techniques and applications of reconnaissance methods to marine mineral deposit characterization. Many of the technological advances made to date have been in direct response to specific requests from industry for drill systems needs, and from federal and state agencies seeking technical support for various research efforts. These cooperative programs have proven to be an extremely efficient and effective way for the MMTC to achieve some of the main program goals that were established for the organization at the outset: primarily, to encourage and assist U.S. industry in marine minerals research activities and to encourage cooperative work among research institutions, government agencies, and industry. The primary achievements of the MMTC/CSD to date include the development of the Remote Placer Drill System for rapid reconnaissance drilling of precious metal placer deposits (including both pneumatic prototype and hydraulic production